Cooperativas de catadores e parcerias com gestores públicos : aspectos promotores de autonomia - França, Lucas Miguel (2012)
This research for the master's degree in Science, Technology and Society (UFSCAR), has as objective to identify to promotional aspects of autonomy in the relations/partnerships established between public managers and enterprises of cooperatives of catadores. Among the highlights methodological procedures to review the literature on the subject and proposed data collection and information from the municipalities, supporting organizations, advisory and involved with cooperatives. The autonomy gain at the time of decisions, the planning activities of the cooperative and other aspects such as monitoring and training are considered essential for the success of experiments involving the use of social technologies and cooperatives. All these points are subject to analysis through the study of partnerships, in this case between public managers and recycling cooperatives in programs for shared management of waste. To develop working partnerships developed were analyzed in the cities of Piracicaba and São Carlos. In both cases respondents identified what are the possible promoting factors and not favoring autonomy in relationships / partnerships between public managers and recycling cooperatives and work done by groups, contributing to the achievement and maintenance of self-management, through the use of analytical categories such as: Decision-makers, degree of democratization in relations, division of labor, Solidarity, public action in the territory, project management, Participation / Coordination, Training networks, Possession of means of production, social, infrastructure investments and sources of revenue of the enterprise. As a result, it was noted that partnerships between cooperatives and managers demonstrate that they have a direct influence on the achievement of autonomy and work in the enterprises, thus hindering the development and ownership by the working groups.